1988
DOI: 10.1203/00006450-198801000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Inhibition of Intestinal Heme Oxygenase by Antibiotics and Tin-Protoporphyrin

Abstract: A B S T R A a . W e assessed the in vivo and in vitro effects of antibiotics and tin-protoporphyrin (TP) on intestinal heme oxygenase (HO) activity using a gas chromatographic assay. This method measures the carbon monoxide produced from heme in the presence of NADPH. After in vivo administration of kanamycin (10 mg/kg body weight), ampicillin (200 mg/kg body weight) or neomycin (60 mg/ kg body weight) with or without T P (65 pmol/kg body weight) to suckling rats, no significant difference in HO activity along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
3

Year Published

1989
1989
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
7
3
Order By: Relevance
“…This phenomenon is less prominent with ZnPP, which accounts most likely for ability of ZnPP to inhibit intestinal HO at light fluxes capable of overcoming inhibition by SnPP. It is not possible to estimate, in retrospect, the light quality and intensity encountered during the previous studies (18,20,21), but our results indicate that the previously observed lack of inhibition of intestinal HO with SnPP could be explained by the fact that HO activity determinations were performed under ambient light (a mixture of indirect summer daylight and cool white fluorescent light ranging in radiant flux from 0.5 to approximately 5 pW/cm2/nm) in clear glass vials. Current activity measurements are performed in amber vials in the dark.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…This phenomenon is less prominent with ZnPP, which accounts most likely for ability of ZnPP to inhibit intestinal HO at light fluxes capable of overcoming inhibition by SnPP. It is not possible to estimate, in retrospect, the light quality and intensity encountered during the previous studies (18,20,21), but our results indicate that the previously observed lack of inhibition of intestinal HO with SnPP could be explained by the fact that HO activity determinations were performed under ambient light (a mixture of indirect summer daylight and cool white fluorescent light ranging in radiant flux from 0.5 to approximately 5 pW/cm2/nm) in clear glass vials. Current activity measurements are performed in amber vials in the dark.…”
Section: Resultscontrasting
confidence: 61%
“…In fact, a higher dose of ZnPP (100 pM) appeared to inhibit intestinal HO (21). Considering our results with tin protoporphyrin (18,20,21), we questioned this finding and further queried whether conditions peculiar to intestinal tissue itself or to our experimental procedure could have influenced the results. Our findings suggest that both possibilities may have played a role and show that all four metalloporphyrins tested can significantly inhibit intestinal HO activity (as measured by CO generation) in vitro, at concentrations as low as 1 pM, under strictly light-limited conditions.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These results contrast with those in the recent report of Hintz et al [ 18] in which no inhibition of intestinal heme oxygenase ac tivity, as determined by carbon monoxide (CO) production in the 13,000-# superna tant, was identified either in vitro or in vivo after SnPP administration at the doses used in this study [ 18]. The disparity between the findings in the previous report [18] and our present results may be due, among other considerations, to the fact that we used mi crosomes in our studies together with exper imental conditions as described by Stohs et al [14], rather than a 13,000-# supernatant, thereby protecting the integrity of the subcel lular fractions prepared from this tissue.…”
Section: Discussioncontrasting
confidence: 57%
“…This dose was selected to match that pre viously used by other investigators [18], Fol lowing oral treatment, heme oxygenase ac tivity was rapidly (within 3 h) inhibited (50% of controls), but the levels returned to normal within 16-24 h after treatment. Fol lowing parenteral treatment, enzyme activity was inhibited to an even greater extent (65% inhibition), and these markedly decreased levels of enzyme activity persisted for at least 48 h after a single dose of the metalloporphyrin.…”
Section: Resultsmentioning
confidence: 99%